2005
DOI: 10.1037/0022-006x.73.2.293
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Autobiographical Memory and Posttraumatic Stress Disorder Following Cancer.

Abstract: In this study, the authors investigated the relationship between autobiographical memory and the onset and maintenance of distressing memories following cancer. In Study 1, participants recently diagnosed with head, neck, or lung cancer were assessed for acute stress disorder (ASD). Participants with ASD reported fewer specific memories than did participants without ASD. In Study 2, the same participants were assessed 6 months later for autobiographical memory and cancer-related posttraumatic stress disorder (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
75
6
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(90 citation statements)
references
References 35 publications
7
75
6
2
Order By: Relevance
“…A cancer diagnosis is often emotionally overwhelming for patients (Gardino and Emmanuel, 2010). Moreover, newly diagnosed patients receive a large amount of new information at the time of diagnosis (Kangas et al, 2005). Kessels (2003) stated that attentional narrowing occurs in events perceived as stressful or emotional.…”
Section: Provision Of Fertility Information By Professional Caregiversmentioning
confidence: 99%
“…A cancer diagnosis is often emotionally overwhelming for patients (Gardino and Emmanuel, 2010). Moreover, newly diagnosed patients receive a large amount of new information at the time of diagnosis (Kangas et al, 2005). Kessels (2003) stated that attentional narrowing occurs in events perceived as stressful or emotional.…”
Section: Provision Of Fertility Information By Professional Caregiversmentioning
confidence: 99%
“…This finding was interpreted as evidence that veterans who maintain a self-image of military identity are more likely to retrieve memories of that part of their lives (McNally, 2003). Similarly, a study of cancer patients with PTSD indicated that these patients retrieved more autobiographical memories about their illness compared to cancer patients without PTSD (Kangas, Henry, & Bryant, 2005). Conway and Pleydell-Pearce (2000) maintain that autobiographical memory for specific events is reconstructed from representations in the autobiographical knowledge base.…”
mentioning
confidence: 97%
“…However, laboratory word tasks are not necessarily an ecologically valid measure of real-life memories of one's personal past, defined as autobiographical memory (Tulving, 2002). Furthermore, disorders such as acute stress disorder, depression, or post traumatic stress disorder (PTSD) that are characterised by cortisol disregulations have been related to recall of nonspecific, over-general autobiographic memories (e.g., Bryant, Sutherland, & Guthrie, 2007;Harvey, Bryant, & Dang, 1998;Kangas, Henry, & Bryant, 2005;Williams & Scott, 1988).…”
mentioning
confidence: 99%